Carina Bifurcation Angle and Side Branch Occlusion in Coronary Bifurcation Lesions Intervention: Angiographic Lesions Characteristic Role in Determining Its Relation - Palinggi, Bogie Putra; Firman, Doni (International Journal of Angiology, 2019)
Side branch occlusion has been implicated as a complication after percutaneous coronary intervention in coronary bifurcation lesions. The role of carina bifurcation angle as one of the characteristics of the coronary bifurcation lesions in causing side branch occlusion after percutaneous coronary intervention is still debated. This study aims to assess the correlation between carina bifurcation angles as one of the characteristics of the coronary bifurcation lesions and side branch occlusion in elective percutaneous coronary intervention. This is a cross-sectional study which utilizes CAAS 5.1 software to measure carina bifurcation angle. We collected 113 lesions in 108 patients that met the inclusion criteria from January 2016 to October 2016. Side branch occlusion occurred in 15 lesions (13.3%), with median carina bifurcation angle 19.17 degrees (p < 0.001). Multivariate analysis showed there is a correlation between carina bifurcation angle with side branch occlusion, OR (odds ratio) 0.86 (95% CI [confidence interval]: 0.80–0.92) with ≤ 33.71 degrees cut off value. Increased risk of side branch occlusion was found in small carina bifurcation angle.
Keywords: Carina bifurcation angle; coronary bifurcation lesions; elective percutaneous coronary intervention; side branch occlusion; plaque shifting; carina shifting; atheromatous plaque